2021
DOI: 10.1016/j.ihj.2021.05.005
|View full text |Cite
|
Sign up to set email alerts
|

Acromegaly: Cardiovascular risk factors, cardiovascular manifestations and early vascular alterations in relation to disease activity

Abstract: Acromegaly is associated with increased cardiovascular morbidity and mortality. 49 acromegaly patients were evaluated for presence of cardiovascular risk factors and manifestations using 2D-Echocardiography, strain, strain-rate, carotid intima media thickness (CIMT) and flow mediated dilatation (FMD) and correlated with disease activity. 32 patients with growth hormone (GH) level >1 ng/ml were considered active. Patients with active disease have more LV dysfunction as assessed by strain(p-0.031) and strain rat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…Studies have demonstrated an association between acromegaly and increased risk of CVD. While the relationship between acromegaly and conditions such as hypertrophic cardiomyopathy, valvular heart disease, arrhytmias and endotelial dysfunction is well established, the association of coronary artery disease and acromegaly is somewhat controversial [5].…”
Section: Introductionmentioning
confidence: 99%
“…Studies have demonstrated an association between acromegaly and increased risk of CVD. While the relationship between acromegaly and conditions such as hypertrophic cardiomyopathy, valvular heart disease, arrhytmias and endotelial dysfunction is well established, the association of coronary artery disease and acromegaly is somewhat controversial [5].…”
Section: Introductionmentioning
confidence: 99%